2020
DOI: 10.1115/1.4047169
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Comprehensive Evaluation of Energy Efficiency of an Oilfield Heating Furnace Based on Combination Weighting Method

Abstract: Abstract The heating furnace is an essential oilfield facility for surface gathering, treatment, and transportation, so the energy consumption level of an oilfield is directly affected by its operational efficiency. In this paper, the thermal efficiency, exhaust gas temperature, external surface temperature, excess air coefficient, and load rate of a heating furnace are taken as energy efficiency evaluation indexes. By improving game theory, the objective and sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…However, China's oilfield facilities are supplied with electricity and heat from the external grid and natural gas boilers separately. Cheng et al adopted the grey TOPSIS method to evaluate the energy efficiency of an oilfield heating furnace, and the results indicated that currently, the efficiency of the furnace was relatively low and needed to be updated for energy saving [12]. The heat pump was utilized by Li et al to recover the lowtemperature waste heat of oilfield sewage [13].…”
Section: Introductionmentioning
confidence: 99%
“…However, China's oilfield facilities are supplied with electricity and heat from the external grid and natural gas boilers separately. Cheng et al adopted the grey TOPSIS method to evaluate the energy efficiency of an oilfield heating furnace, and the results indicated that currently, the efficiency of the furnace was relatively low and needed to be updated for energy saving [12]. The heat pump was utilized by Li et al to recover the lowtemperature waste heat of oilfield sewage [13].…”
Section: Introductionmentioning
confidence: 99%